Defi-crime: condition, trends and criminological models - E. L. Sidorenko (Russian Journal of Economics and Law)
Objective: to develop a criminological concept of DeFi-crime and measures to deter it.Methods: dialectical materialism and the general scientific methods of cognition based on it, used in the Russian criminology.Results: a criminological concept of DeFi-crime as a type of digital crime was developed, i.e. a new specific criminological theory of DeFi-crime (DeFi-criminology) within the structure of digital criminology was proposed. The information factors influencing the DeFi-crime state, structure and trends were determined, and measures for its deterrence by criminological and technological means were proposed.Scientific novelty: the presented work is the first and only study conducted within the framework of digital criminology, reflecting the state, trends and structure of DeFi-crime, revealing the main causes that form it, as well as describing options for deterring this type of digital crime by technological and criminological means.Practical significance: the study results can be used in law enforcement activities when assessing potential threats from DeFicrime and developing measures to reduce them; in educational activities – in the process of teaching courses in criminology, cybercriminology, digital criminology; in research activities – when obtaining additional knowledge on certain types of DeFi–crime: DeFi-theft and DeFi-fraud during their further research in DeFi-criminology.